Consumer Behavior Toward Sustainable Branding Strategies in Rural Markets: Systematic Literature Review - Nadifah, Dhofirotun; Muhammad Saiful Hakim; Muhammad Ubaidillah Al Mustofa (Universitas Airlangga, 2025)
Sustainable branding has become a critical approach to rural markets, whose consumer behavior is defined by the peculiar socio-economic situation, the traditions of a culture, and environmental issues. Although the subject is receiving increased interest, little research exists that has established the correlation between bibliometric trends and empirical research on the reactions of rural consumers to sustainability efforts. Conceptual models or isolated case studies have been investigated in most studies; little has been done in establishing the relationship between thematic research clusters and actual rural market practices. The gap present in this study is that many studies have been conducted to determine the impact of information and knowledge systems on organizational performance and management in the past seven years (2015-2025), yet these studies were not anchored on a systematic literature review (SLR). To meet this gap, the current article merges both bibliometric analysis and systematic literature review (SLR) of 182 publications conducted in the last seven years (2015-2025) and uses R-Biblioshiny and VOSviewer to detect thematic clusters, patterns, and research Results indicate that the average annual publication increase is 6.39 percent, with China, India, and Indonesia as the leading nations and indicate 5 key themes, namely: green marketing adoption, sustainable branding in developing regions, corporate sustainability and trust, consumer behavior, and CSR in regional contexts. Empirical data have shown that rural consumers focus more on affordability, quality of products, health and safety, environmental commitments related to culture, but have difficulty accessing them, lack sustainability literacy, and do not trust brand claims. The theoretical contribution of the study is that it correlates bibliometric clusters with consumer behavior in rural areas and provides practical advice on how to create transparent, inclusive, and culturally responsive sustainability strategies.